Introduction to OneCGIAR Genetic Innovations Action Area & the Accelerated Breeding Initiative - Das, Biswanath (2023)
Presentation given by Biswanath Das during a partner meeting that took place in Istanbul, Turkiye, 13-15 December 2022 between ICARDA management and NARES leaders, selected based on their active role in requesting, using, and promoting ICARDA’s Genetic Innovations. ICARDA sought guidance from its NARES partners to determine if the portfolio of Genetic Innovation research defined in the 2017-2026 ICARDA Strategy is still significant to the 2030 horizon set by the CGIAR. As part of this initial engagement in CWANA++, this meeting provided the first step towards further inclusion of other involved CGIAR Centers. In their initial deliberations, NARES have expressed the following considerations to guide this prioritization work: food security, climate change, and strategies to support effective management of agriculture and food systems.